From Chaos to Cosmos: Theological Insights on Creation Narratives in Patristic Literature - Adeoye, Moses Adeleke (RaSAIL Media Group, Semarang, Indonesia, 2024)
This study investigates the development of creation narratives within Patristic literature, focusing on key theologians from the Apostolic to Medieval periods, such as Augustine, Origen, and Gregory of Nyssa. The primary issue explored is the theological theme of chaos and cosmos, which illustrates how God transforms chaos into order through His creative and redemptive actions. The research traces how early Christian thinkers understood and articulated this theme, particularly about God's kingship and the overarching narrative of creation, fall, redemption, and new creation. The study employs a qualitative textual analysis of prominent Patristic writings, systematically reviewing key texts that discuss creation narratives. This method allows for a detailed examination of the theological nuances present in these works, highlighting significant trends and variations in thought among different theologians. The iterative approach of this analysis uncovers the dynamic nature of early Christian cosmology and its implications for Trinitarian theology. The findings reveal that Patristic thinkers were deeply concerned with establishing a solid theological foundation for understanding creation about the Trinity. Their reflections continue to enrich contemporary Christian thought on creation, offering insights relevant to modern spiritual and theological discussions. This study recommends further engagement with Patristic literature to foster interdisciplinary dialogue, historical contextualisation, and meaningful theological reflection on creation in the context of contemporary issues.